2020
DOI: 10.18549/pharmpract.2020.3.2000
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacists´ interventions in the management of type 2 diabetes mellitus: a systematic review

Abstract: Background: Type 2 diabetes mellitus is a chronic disease that is reaching epidemic proportions worldwide. It is imperative to adopt an integrated strategy, which involves a close collaboration between the patient and a multidisciplinary team of which pharmacists should be integral elements. Objective: This work aims to identify and summarize the main effects of interventions carried out by clinical pharmacists in the management of patients with type 2 diabetes, considering clinical, humanistic and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(122 reference statements)
1
19
0
Order By: Relevance
“…In addition, our study reveals improvement in glycaemia in the intervention cohort, which may partly be linked to improved adherence to recommended therapies in the cohort compared to the control group. Though, the average HbA1c value in our study is above the American Diabetes Association (ADA) recommended target of < 7.0% [ 42 ], however, significant reduction (0.9%) in the average HbA1c from 8.7 ± 1.5% (baseline) to 7.8 ± 2.0% (6-month post-baseline) in the intervention group is consistent with previous studies in most developed and some developing countries [ 30 , 32 , 33 ]. Kiel et al in an observational prospective study to demonstrate the pharmacist’s impact on clinical outcomes in a diabetes disease management program showed an HbA1c reduction of 1.6% [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our study reveals improvement in glycaemia in the intervention cohort, which may partly be linked to improved adherence to recommended therapies in the cohort compared to the control group. Though, the average HbA1c value in our study is above the American Diabetes Association (ADA) recommended target of < 7.0% [ 42 ], however, significant reduction (0.9%) in the average HbA1c from 8.7 ± 1.5% (baseline) to 7.8 ± 2.0% (6-month post-baseline) in the intervention group is consistent with previous studies in most developed and some developing countries [ 30 , 32 , 33 ]. Kiel et al in an observational prospective study to demonstrate the pharmacist’s impact on clinical outcomes in a diabetes disease management program showed an HbA1c reduction of 1.6% [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…The challenge of treatment non-adherence among these patients may perhaps be averted if patients are adequately counseled on the necessity for optimal commitment to prescribed therapies, while non-adherent behaviours appropriately resolved [27][28][29][30]. Studies in many developed countries have reported improvement in medication adherence and clinical outcomes in pharmacist-conducted medication management among patients with diabetes [29,[31][32][33]. Also, it has been shown that a high level of medication adherence is associated with lower disease-related medical costs [12,34].…”
Section: Introductionmentioning
confidence: 99%
“…4 Systematic reviews and meta-analysis of randomised controlled trials have demonstrated the effects of pharmacist-led care in patients with T2DM, but majority of these studies were conducted in high income countries (HICs) and only complimented by few from LMICs. [4][5][6][7][8][9][10][11][12] Literature search identified four published randomised-controlled trials among patients with DM in Nigeria within the last decade. [13][14][15][16][17] None of the study was done in the northern part of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence regarding the involvement of pharmacists in the chronic management of type 2 diabetic patients is limited and heterogeneous, albeit positive. In general, in studies where pharmacists were involved in the diabetes care team, a significant improvement in therapeutic outcomes, and a reduction in hospitalizations and consumption of resources were observed [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These effects are more evident when prescription abilities are ascribed to the pharmacist (an activity not allowed by Italian law).…”
Section: Discussionmentioning
confidence: 99%